Delivery of siRNA using novel conjugates for cancer therapy. - Guo, Venetia Yixin. (2010)
Short interfering RNAs (siRNAs) trigger RNA interference (RNAi). This offers great potential as a novel therapeutic treatment based on its highly specific silencing of the encoded protein. A major barrier to the advancement of siRNA therapies is the development of delivery carriers capable of effective and nontoxic delivery in vivo. In this study, two derivatives of an anticancer agent Organically-Derived Molecule 1 (ODM1) -(PEG-ODM1 and O-ODM1), were investigated as potential siRNA carriers for their synergistic effects with therapeutic siRNAs for cancer therapy. The interactions between ODM1 and siRNA were characterized, the functionality and subcellular localization of delivered siRNA was investigated, and cytoxicity of the system was determined. The results highlighted the non-ionic interactions between ODM1 derivatives and siRNA as a novel approach to siRNA delivery as ODM1 derivatives are non-charged molecules. Cell viability assay revealed that ODM1 derivatives are nontoxic following delivery. In addition, investigations of gene silencing illustrated that ODM1 derivatives-mediated siRNA delivery resulted in downregulation of the target gene expression, suggesting the functionality of delivered siRNA. These preliminary results highlighted the promise of the construct as potential nanocarriers for in vivo siRNA delivery for therapeutic purposes.